Selling Guantánamo: exploding the propaganda surrounding America's most notorious military prison - Hickman, John (Univ. Press of Florida)
Challenges the U.S. government's official explanation for keeping hundreds of POWs from the War in Afghanistan in continued custody at Guantanamo